A pesquisa de imagem em fóruns de discussão online: o caso da Eletronic Arts no Reddit - Teixeira, Glean de Oliveira (Brasil, 2020)
In 2017 the publisher Electronic Arts (EA) went through a crisis after responding in a controversial manner on an online forum aggregator known as Reddit. A fan questioned financial procedures allegedly underhanded by the company on it’s new game. The crisis surpassed the aggregator barriers, because EA’s answer became the most downvoted on Reddit’s history, attracting attention from the specialized media. The company then gave an official response, aiming to soften the crisis, modifying the procedures criticized by fans. The thread on the forum resulted in the publishing of 2800 fans comments about the situation and Electronic Arts. This research then asks if the said discussion could be useful in an image research, given that the nature of those comments revealed how members of the forum felt not only about the situation, but also about the company as a whole. To do so, was adopted an alternative methodology over traditional image research methods, aiming an adaptation to the forum context. The digital ethnography, or netnography, was chosen consediring it’s adequacy to the analysis of online communities. Then the 628 most upvoted comments by the forum members were chosen as sample. These were collected and analyzed in accord to netnographycal and Public Relations practices, specifically, concepts of image, reputation and networks. The conclusions were that the thread produced comprehensions on Eletronic Arts’s image on the forum and the reasons to such. The results also allowed comprehension on the involved public profile, the forum’s culture and conclusions regarding the possibilities of the netnographycal tool as research method to Public Relations.